Performance of new 8-inch photomultiplier tube used for the Tibet muon-detector array. (30th June 2016) - Zhang, Y.; Huang, J.; Chen, D.; Zhai, L.-M.; Chen, X.; Hu, X.-B.; Lin, Y.-H.; Jin, H.-B.; Zhang, X.-Y.; Feng, C.-F.; Jia, H.-Y.; Zhou, X.-X.; et al.
Abstract: Since 2014, a new hybrid experiment consisting of a high-energy air-shower-core array (YAC-II), a high-density air-shower array (Tibet-III) and a large underground water-Cherenkov muon-detector array (MD) has been continued by the Tibet AS γ collaboration to measure the chemical composition of cosmic rays in the wide energy range including the ``knee''. In this experiment, YAC-II is used to select high energy core events induced by cosmic rays in the above energy region, while MD is used to estimate the type of nucleus of primary particles by measuring the number of muons contained in the air showers. However, the dynamic range of each MD cell is only 5 to 2000 photoelectrons (PEs) which is mainly designed for observation of high-energy celestial gamma rays. In order to obtain the primary proton, helium and iron spectra and their ``knee'' positions with energy up to 10 16 eV, each of PMTs equipped to the MD cell is required to measure the number of photons capable of covering a wide dynamic range of 100–10 6 PEs according to Monte Carlo simulations. In this paper, we firstly compare the characteristic features between R5912-PMT made by Japan Hamamatsu and CR365-PMT made by Beijing Hamamatsu. If there exists no serious difference, we will then add two 8-inch-in-diameter PMTs to meet our requirements in each MD cell, which are responsible for the range of 100–10000 PEs and 2000–1000000 PEs, respectively. That is, MD cell is expected to be able to measure the number of muons over 6 orders of magnitudes.